Employee Performance in Satbrimob Polri Primary Clinic, East Java: The Roles of Digital Public Services, Work Culture, and Competence - Utomo, Asih Purwanto Budi; Purwanto, Purwanto; Rahayu, Sri; Sundjoto, Sundjoto (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study analyzes the relationship between public service digitalization, organizational culture, and employee competence in explaining performance levels at the Satbrimob Polri Primary Clinic in East Java. Amid accelerating technological innovation and heightened expectations for public healthcare delivery, institutions are increasingly required to integrate digital solutions with effective human resource management. Adopting a quantitative methodological framework, this research evaluates how technological adoption, shared workplace values, and professional skillsets jointly shape employee performance within a healthcare unit affiliated with law enforcement. Data were collected through structured questionnaires distributed to all clinic personnel and analyzed using regression-based statistical techniques. The findings indicate that digitalization and competence serve as primary contributors to performance improvement, enabling employees to perform tasks more efficiently, accurately, and responsively. While work culture supports performance development, its role appears secondary when assessed alongside technological and competency factors. Notably, digitalization stands out as the most influential element, underscoring the importance of integrated digital systems in modern public service operations. These results suggest that performance enhancement in public healthcare organizations depends on the synergy between technology utilization and continuous competency development rather than reliance on organizational norms alone. This study contributes to theoretical and practical discussions in public sector human resource management by offering empirical insights from a specialized institutional setting and highlighting strategic directions for sustainable performance improvement.